Assessment of compression forces in a digitally modified short leg cast for pressure injury risk monitoring in healthy children - Vrankovic, Matia Iva; Annaheim, Simon; Willibald, Jana; Lieber, Jan; van Hedel, Hubertus J. A.; Schlüer, Anna-Barbara; Rossi, René M.; Meyer-Heim, Andreas (Frontiers in Pediatrics, 2024)
Objective: Casting is an essential treatment for neuro-orthopedic conditions in children with cognitive, sensory, and communicational disabilities. However, a main side-effect is the development of pressure injuries, resulting in additional (wound) therapies and prolongation of the hospital stay. The primary aim of our study was to investigate the potential of objective pressure measurements in casts to assess the risk for pressure injury development. Methods: Five pediatric healthy participants were included in this study. We measured the global and the local compression force at body sites prone to pressure injury development for different body positions and the transfer in-between in a cast equipped with pressure sensors. These conditions resulted in partial or full body weight loading.The global maximum compression force was affected significantly by body postures with partial and full loading of the cast and during transfer. The local compression force significantly correlated with the global compression force at the heel and instep area.Integrating sensing technologies into casts bears a high potential for early recognition of critical conditions inside the cast and inducing preventive measures in the at-risk population.